Study of Gibberellic Acid Production by Solid State Fermentation Using Fusarium Moniliforme Sheldon - Panchal, Rakeshkumar Ramanlal; Desai, Piyushbhai Vishnubhai (International Journal of Applied Sciences and Biotechnology, 2016)
Gibberellic acid production using Fusarium moniliforme, isolated from wilted sugarcane plant has been investigated by solid state fermentation (SSF). The gibberellic acid production of 154mgm/gm was obtained on commercial wheat bran (CWB) mineral salt acid bed in 500 ml flasks after 168 h incubation. The gibberellic acid production rate was about 0.6 to 0.9 mgm/gm/hr during 96 to 168 h. Different carbon sources namely sucrose, lactose, maltose, soluble starch, glycerol, wheat flour and maize flour were tested as an additional substrate along with CWB at the concentration of 25% w/w or v/w base to observe its effects on gibberellic acid production. Soluble starch has been proved the best additional carbon source for gibberellic acid production, which yielded 1160mgm/gm of gibberellic acid after 168 h. Similarly, various nitrogen sources namely NH4Cl, NH4NO3, (NH4)2SO4, (NH4)MoO4 and urea were tested as an additional substrate at the concentration of 0.07% w/w of CWB. Urea was proved as the best nitrogen source which yielded 532 mgm/gm of gibberellic acid after 168 h incubation. We have observed about 7.5-fold and 3.5-fold increase in gibberellic acid production upon addition of soluble starch and urea respectively, in CWB using Fusarium moniliforme. Int J Appl Sci Biotechnol, Vol 4(3): 402-407